ANALISIS KEMAMPUAN PENDIDIK DALAM MENERAPKAN PENILAIAN AUTENTIK PADA MATA PELAJARAN BIOLOGI KELAS X IPA SMA DI KABUPATEN LOMBOK TIMUR - LL. Zainal Haqiqi; Agus Ramdani; Lalu Zulkifli (Postgraduate, University of Mataram, 2018)
This study aims to know the abilities of the teachers in applying authentical assessment in biology at grade X IPA Senior High School of Lombok Timur district. This study using descriptive method which getting data in the verbal only not in numbers. Getting samples at 8 Senior High Schools of Lombok Timur district which aplicate kurikulum 2013 they are SMAN 1 Masbagik, SMAN 2 Aikmel, SMAN 1 Sikur, SMAN 1 Terara, SMAN 2 Selong, SMAN 1 Keruak, SMAN 1 Montong Gading and SMAN 1 Sakra. To these teachers of biology were given instruments which asked how the authentical assessment reseach done in the schools and the result were presented in this study. The ability of teachers in applying authentical assessment were different from every questions there are attitude, knowledge and skill. Attitude they are observations, self assessment, assessment among students, journal and interview were answered by teachers with yes 65,62% , knowledge were answered by teachers by yes 88,75% and skill were answered yes 87,75%. Ability of teachers in applying authentical assessment were answered yes as many as 78,75% and the next verbally answered by teachers because of the problems in applying authentical assessments. Constraintburden of teachers in design and applying authentical assessment were given 5 questions and the interview of the execution of authentical assessments were given about 91 questionsAutentical assessment, biology